Analisis Kesulitan Belajar Siswa Kelas VI Sekolah Dasar pada Materi Operasi Hitung Bilangan Bulat - Diajeng Arta Anenda (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This research aims to determine the ability to understand mathematical concepts in class VI students at SDN 01 Bantan in the material on integer counting operations, find out the difficulties that students experience in understanding mathematical concepts in the material on integer counting operations, find out the factors that cause students' difficulties in understanding the material. as well as efforts to overcome difficulties in learning material on integer arithmetic operations. The type of research used is qualitative research. The data collection techniques used were observation and interviews. The results of the research show that students experience difficulties in operating addition, subtraction and multiplication of integers, as well as internal factors such as students' lack of interest in learning mathematics, and students' levels of understanding that are not the same or different. Therefore, teachers have an important role in helping students succeed in understanding and understanding the material on integer counting operations by linking integer counting operations in the form of games so that students have fun learning and are easy to understand.